Water immersion as a recovery aid from intermittent shuttle running exercise - Corbett, J.; Barwood, M. J.; Lunt, H. C.; Milner, A.; Tipton, M. J. (European Journal of Sport Science, 2012)
To investigate the effect of different water immersion (WI) treatments on recovery from intermittent shuttle running exercise in comparison to an ecologically relevant control. Methods: Forty males performed 90 minutes intermittent shuttle running, following which they were assigned to either: (1) 12-min standing WI at 12°C; (2) 12-min standing WI at 35°C; (3) 2-min seated WI at 12°C; (4) an ecologically relevant control consisting of 12 minutes walking at 5 km h-1. Muscle soreness, maximal voluntary contraction (MVC) of the knee flexors and extensors, hop distance, creatine kinase activity and myoglobin concentration were measured before exercise and in the 168 hours following the intervention. Between-group differences, time effects and interaction effects were investigated by mixed-model ANOVA. Results: The shuttle running exercise induced an increase in muscle soreness (1, 24, 48 and 72 hours post-intervention) creatine kinase activity and myoglobin concentration (post-exercise and 1, 24 and 48 hours post-intervention), and reduced MVC of the knee extensors (11% reduction at 24 hours, remaining reduced at 48 and 72 hours), flexors (24% reduction at 24 hours, remaining reduced at 24, 48, 72 and 168 hours), and hop distance (24 and 48 hours). However, no between-group differences or interaction effects were evident for any of these parameters. Conclusion: The WI protocols investigated were not better than light exercise in facilitating recovery from shuttle running exercise. Future studies examining the efficacy of WI as a recovery intervention should include a representative control condition to increase their relevance to sporting populations.